2020
DOI: 10.1016/j.jadohealth.2019.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Combustible Cigarette Use in Adolescence: Links With Adjustment, Delinquency, and Other Substance Use

Abstract: Objective: Identify proximal links between e-cigarette use and numerous indicators of adjustment, delinquency, and other substance use in adolescence, beyond prior levels and confounders. Method:The ongoing Millennium Cohort Study is a nationally representative, intergenerational, longitudinal study of children born 2000-2001 in the United Kingdom followed from birth to age 14 (n=11,564 adolescents and their parents). A series of OLS and logistic regressions compared 14-year old e-cigarette only users to never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…than children, which is consistent with the study of Staff, J. [42]. However, the prevalence of diarrhea in this study was close to that of the previous study (24.8%) [43].…”
Section: Discussionsupporting
confidence: 92%
“…than children, which is consistent with the study of Staff, J. [42]. However, the prevalence of diarrhea in this study was close to that of the previous study (24.8%) [43].…”
Section: Discussionsupporting
confidence: 92%
“…Results from three new studies in this issue of the Journal of Adolescent Health suggest that adolescent mental health is another important aspect linked to e-cigarette use. A study by Staff et al [26] showed that adjustment problems, delinquent behavior, and substance use were associated with adolescent dual users (those using both e-cigarettes and cigarettes) and e-cigaretteeonly users, compared with nonusers. The study by Veliz et al [10] showed that adolescent dual use of ecigarettes likely contributed to tobacco and substance use disorders.…”
Section: Editorialmentioning
confidence: 99%
“…A third study used a national sample of U.S. adults and found associations of risky alcohol use with dual cigarette and e-cigarette users and e-cigarette only users compared with nonusers (Roberts et al, 2020). Despite scarce prospective research, cross-sectional studies suggest associations of e-cigarette use with alcohol and other substance use (Demissie et al, 2017;McCabe et al, 2017;Miech et al, 2016;Staff et al, 2020;Wills et al, 2015). For example, in a national sample of U.S. high school students, those who used e-cigarettes were more likely to also use alcohol and to binge drink (Demissie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%